Quasicrystals: The State of the Art - DiVincenzo D P (World Scientific, 2000)
An introduction to quasicrystals for mathematicians, physicists, materials scientists and students. The original intent was for the book to be a progress report on developments in the field. However, the authors sought to adopt a broad, pedagogical approach focusing on points of lasting value. Many subtle and beautiful aspects of quasicrystals are described, in a way that should be useful to both the expert and the student. In this second edition, some authors have appended short notes updating their essays. Two new chapters have been added. Chapter 16, by Goldman and Thiel, reviews the experimental progress since the first edition (1991) in making quasicrystals, determining their structure and finding applications. In Chapter 17, Steinhardt discusses the quasi-unit cell picture, a promising approach for describing the structure and growth of quasicrystals in terms of a single, repeating, overlapping cluster of atoms.